PAI Alumni IAIN Syekh Nurjati Cirebon's Efforts to Maintain Tolerance - Muthoharoh Muthoharoh (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Tolerance in a diverse society of ethnicity, race, religion, and culture is an attitude of absolute openness to accept without devaluing, reducing, equating others, or making the difference an alter-ego. The purpose of this research is to describe and analyze PAI Alumni IAIN Syekh Nurjati Cirebon's efforts to maintain tolerance. The data is presented in descriptive form using qualitative methods to assess the validity of the data through triangulation. The research included alumni from the 2019 graduating class, with 40 alumni from each of the respondents. Data is gathered through interviews, observations, and documentation. The collected data is then described. Based on the findings of observations, interviews, and data triangulation, it was discovered that PAI IAIN Syekh Nurjati alumni contributed to the community's tolerance of religious communities. As a follow-up to this research, synergistic collaboration between universities and alumni as partners is required in order to maintain harmony and tolerance between religious communities.